Effort For A Better Life Of Waris Dirie Autobiography Reflected On Waris Dirie's In Desert Flower (2012) :An Individual Psychological Approach - Windrawati, Agustina Kurnia; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, M.Pd (2014)
The research is proposed to analyze how the effort for a better life of Waris Dirie Autibiography reflected on Waris Dirie's in Desert Flower 2012 by Individual Psychological Approach. There are two objective: the first is to analyze the novel in term of structural elements, and the second is to analyze the novel based on the individual Psychological Perspective. This study is a qualitative study, using Waris Dirie's Desert Flower novel 2012 as of structural elements, and the secondary data. The primary data source is Desert Flower novel which is writen by Waris Dirie, and the secondary data are some articles, book of literary and internet related to the subject. The method of collecting data in this research is library research by reading the novel, reading some related books and articles, accessing internet, taking notes of important part, arranging, and drawing conclusion the data. In analyzing the data, the writer employs descriptive analysis. Structural elements of the novel consist of character and characterization of the major and minor character. This is a true story and also as an autobiography of Waris Dirie's life. Setting of place most in Africa and London. Setting of time since in 1965 until 1998. Point of view of this novel to the respective of the story teller, it uses the first person. The plot of story begins from the exposition when she was a little girl, then the middle is complication when she was about 13, her father announced that she would be married to a man in his 60s. And the end happens when Waris comes back to Somalia, she has been a supermodel, then met her mother. The outcome of the study shows that the novel illustrates the effort for a better life. Waris Dirie shares her story and her impressing and distressing journey from growing up as a nomadic child who was tragically circumcised, to living on her own in London, becoming a well heard of model, although finding some obstacles she should work hard and strugle to earn money of herself and family finally being appointed Ambassador for the Elimination of Female Genital Mutilation.